The Effectiveness of Wet Cupping Complementary Therapy to Decrease Blood Pressure in Hypertension Patients at Kolaka - Lusiana Jeni; Tahiruddin Tahiruddin; Cholic Harun Rosjidi (LPPM STIKes Karya Kesehatan, 2023)
Abstract. Cupping is one of the complementary therapies that can reduce blood pressure in people with hypertension. Wet cupping therapy is a cupping process by making a fine incision or stabbing to remove dirty blood in the epidermal capillaries and plays a role in controlling vasodilation so that blood pressure can decrease. The purpose of this study was to determine the effectiveness of complementary wet cupping therapy on reducing blood pressure in hypertensive patients at the Pomaala Public Health Center, Kolaka Regency. This study is a quantitative study, with a quasi-experimental design with a